Privileging One's Own? Voting Patterns and Politicized Spending in India. (March 2023) - Jensenius, Francesca R.; Chhibber, Pradeep
How do politicians allocate public resources? Despite the extensive literature on distributive politics, we have limited micro-level evidence for why and under what circumstances politicians choose various allocation strategies. India's discretionary constituency development scheme (MPLADS) provides an excellent opportunity to study the spending choices of individual politicians. Drawing on an original dataset linking voting patterns across 227, 507 villages in the 2009 general elections to MPLADS allocations 2009–2014, we find that politicians generally channel more projects and resources to villages that vote for them in higher numbers. We then leverage a natural experiment created by the delimitation (redistricting) of electoral boundaries in 2008 to provide causal evidence that spending choices are driven by short-term electoral incentives. Finally, we show that allocation patterns differ by the type of party that has brought a politician to power. Our findings contribute to the growing literature on heterogeneity in politicians' distributional choices.